Renewable Energy and Poverty in Sustainable Development of the European Union - Mlaskawa, Julita (Problemy Ekorozwoju, 2022)
The current socioeconomic development results in a number of consequences that lead to changes in the environment. These changes are often harmful and are associated with over- or misuse of natural resources. The issue of sustainable development is increasingly taking a prominent place in regional and local development strategies. Access to energy services is essential for social inclusion. Addressing poverty, including energy poverty, can bring a number of benefits related to reduced health expenditures, reduced air pollution, improved comfort and well-being, and improved household budgets, among other things. According to the results of the analysis, the utilisation of energy from renewable sources is intrinsically linked with the salary level – on average, a higher salary level is accompanied by a larger scale of utilising energy from renewable sources. In spite of the expected negative value, a similar relationship has been observed in the case of correlating the level of poverty with the use of energy from renewable sources – it is higher when the use of energy from renewable sources is higher. The performed study indicates the lack of adequately constructed support mechanisms for the poor in terms of financing and operating installations generating green energy, as well as the lack of proper education as regards local and global benefits resulting from prosumer energy. The desire to eliminate the abovementioned barriers necessitates the continuation of actions concerning synergistic accomplishment of the first and seventh targets, constituting two out of seventeen foundations of sustainable development.